137k views
1 vote
(3t^1/6)^3(2t^0)^-3

I really need help simplifying this, please help!!

1 Answer

5 votes


\bf \begin{array}{llll} \textit{negative exponents} \\\\ a^(-n) \implies \cfrac{1}{a^n} ~\hspace{8em} \end{array} \begin{array}{llll} \textit{rational exponents} \\\\ a^{( n)/( m)} \implies \sqrt[ m]{a^ n} \end{array} \\\\[-0.35em] \rule{34em}{0.25pt}


\bf \left( 3t^{(1)/(6)} \right)^3 (2t^0)^(-3)\implies \left( 3^3 t^{(1)/(6)\cdot 3} \right) (2(1))^(-3)\implies \left( 27t^{(1)/(2)} \right) 2^(-3)\implies \cfrac{27t^{(1)/(2)}}{2^3} \\\\[-0.35em] \rule{34em}{0.25pt}\\\\ ~\hfill \cfrac{27√(t)}{8}~\hfill

User Sarabjit
by
4.4k points